Swift heavy ions modification with polymer composites: A Review. Issue 1 (1st May 2022) - Kaur, Kiranjot
Abstract: In this review paper the focus is to summarize the study of variation in optical, electrical, structural and morphology properties of swift heavy ions of polymer composite. Polyaniline is mainly used in the electrical and electrochemical properties. The synthesis techniques such as chemical oxidative method, electrochemical method, sol-gel method, doping method and many other techniques were used to prepare polyaniline composites. The variation in optical properties can be analysed with the help of UV-Vis and photoluminescence spectroscopy. The structural and morphology can be analysed with the help of FTIR and SEM (scanning electron microscope). The crystal structure, lattice constant and d-spacing can be analysed with the help of XRD.